Approaches On Virtual Education In The Face Of Social Isolation Measures By Covid-19 In A Teacher Training School - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Currently virtual education takes on a priority and fundamental role in the face of social isolation measures in higher education institutions that train teachers, where only face-to-face education was authorized, virtuality being a new and novel process in Peru. The research was of a qualitative approach, oriented to the fundamental understanding of phenomena, observable facts and the relationships established between people, it was characterized by being systemic due to its emergent, complex nature, and built in the methodological process of the becoming of the work, the method used was virtual ethnography in education, online research method, participant observation techniques and the interview were used, the instruments used were the in-depth interview adapted through colloquial and recorded dialogues with the informants; The field diary allowed observing and recording the educational practice of the participants through virtuality, there was the participation of 12 informants among managers, teachers and students, the data analysis was done through the Atlas ti 8, the conclusion Principal reports that the approaches of the virtual educational community have been modified over time, becoming a permanent, autonomous and cooperative learning evidenced in coexistence and interaction as a virtual community, highlighting the solidarity and commitment of its members towards virtual education and at a distance.